MONITORING DAN UPAYA MENGENDALIKAN MUKA AIR PADA PERKEBUNAN DI LAHAN RAWA GAMBUT DI INDONESIA - Budi Triadi; Parlinggoman Simanungkalit (JURNAL TEKNIK HIDRAULIK, 2018)
Drainage construction for  plantations development on peatlands often caused controversy. Dranage construction will be followed by subsidence of peatland. To be able to extend the chance to get profit in the plantation business subsidence prevention efforts are needed. Setting water level and the prevention of excessive drainage is one of the efforts to reduce the rate of subsidence of the peat. This study is based on literature review by collecting information from various sources and then comparing and analyzing it so that information is obtained on a comprehensive subject matter. Literature review include: monitoring parameters, types of equipment for monitoring, pattern placement monitoring equipment, the range and the frequency of monitoring. From the study concluded that the water level necessary to measure on land and channels using dipwell and staff gauges. Observations were made with a combination of automated  recording device and manual recording. Both are quite accurate, but the use of automatic registers in remote locations saves time, and if an automatic device is installed in an area that has the potential to have large water level fluctuations and runs quickly, it will provide more accurate data. Observations on dams for water level control are installed at every 20 cm drop in hidraulic head.